Potential Vaccine Targets for COVID-19 and Phylogenetic Analysis Based on the Nucleocapsid Phosphoprotein of Indonesian SARS-CoV-2 Isolates - Muhammad Aldino; Renadya Maulani; Rasyadan Probojati; Viol Dhea Karisma; Arif Nur Muhammad Ansori; Arli Aditya Parikesit (Universitas Gadjah Mada, 2021)
Recently, the world is facing the outbreaks of severe acute respiratory syndrome coronavirus 2 or SARS-CoV-2 and the number of infected patients is increasing every day. Researchers are doing their best to find the most effective treatment to tackle this deathly virus. Several approaches had been proposed to be tested in the lab for the efficacy but none of them are qualified to be use as the treatment of the COVID-19. Therefore, the aim of this study is to design a vaccine based on epitope, which were obtained from the nucleocapsid phosphoprotein (N protein). In addition, 38 samples of SARS-CoV-2 Isolates were being retrieved from the GISAID Database and NCBI GenBank. Later on, these samples will be used for checking the evolutionary relationship of the SARS-CoV-2 and also, to determine whether this nucleocapsid proteins are well-conserved (less or even no mutations occur at all) and whether there was any evolutionary relationship between the recent coronavirus with the previous coronavirus by conducting the phylogenetic analysis. Then, we wanted to see the molecular interaction between the human BCR/FAB receptor with the predicted peptides through the molecular docking process. All of the peptides were generated by the IEDB analysis tools and have already been tested for the antigenicity, so the one that was being docked are the peptide that has antigen properties. Based on the analysis that had been done, we would like to recommend the PEP1 as an epitope-based peptide vaccine candidate to deal with the SARS-CoV-2 outbreaks.